Father's Love Reflected in Danielle Steel's Winners (2013) Novel: A Humanistic Psychological Approach - RISTANTI, Kristi, Dr. Phil. Dewi Candraningrum, M.Ed, Titis Setyabudi, S.S. M. Hum (2015)
The major problem of this study is how a father shows her love to his children. Father's love is one of greatest influences for children development. The objective of this study is to analyze Danielle Steel's Winners based on the structural elements and analyze this novel based on the humanistic psychological Approach. The Writer employs qualitative method. The writer uses two data sources: primary and secondary. The primary data source is about the novel itself. Then, the secondary data sources are the books about humanistic psychological, references from internet about Winners, and other sources, which are have relation to the analysis. The method of data collection is library research and the technique of data collection is descriptive technique. Based on the analysis, the writer gets some conclusions. The study shows that there is a father's love which is so great in the story of Winners novel. It can be known from Bill Thomas, he is a father. He has a daughter, Lily Thomas. Bill adores Lily so much. Bill's love as a father can be seen from Lily's life. Lily Thomas can pass the four needs (Physiological needs, Safety needs, Love and Belongingness needs, Esteem needs) and has the fifteen characteristics of Self-actualization. Because of a father's love, Lily can fulfill her needs. Bill Thomas has fulfilled all of her needs. He always supports Lily to be the best one.